Peran Infeksi Bakteri Patogen pada Jalur Inflamasi dalam Patogenesis Kolitis Ulseratif: Tinjauan Pustaka - Lismayana Hansur; Paisal (PT Dexa Medica, 2026)
Ulcerative colitis is a chronic inflammatory bowel disease characterized by mucosal inflammation of the colon. Recent evidence highlights the significant role of gut microbiota dysbiosis and pathogenic bacterial infections in the pathogenesisand progression of the disease. Methods: This study was a literature review conducted through a systematic literature search using PubMed, Scopus, and Google Scholar databases, covering publications from 2014 to 2024. The searchfocused on the involvement of pathogenic bacterial strains and immune-inflammatory mechanisms. Results: Several bacteria, including Bacteroides fragilis, pathogenic Escherichia coli, and Klebsiella species, are known to disrupt intestinal mucosal integrity and trigger inflammation through activation of inflammasome and the interleukin (IL)-17/IL-23 cytokine pathways. Dysbiosis also leads to decreased production of protective metabolites such as short-chain fatty acids (SCFAs).Conclusions: A comprehensive understanding of the interactions between pathogenic bacterial infections, gut microbiota dysbiosis, and host immune responses is crucial for the development of diagnostic and personalized therapeutic strategies in the management of ulcerative colitis.